Alternate pathways for processing in the internal transcribed spacer 1 in pre-rRNA of Saccharomyces cerevisiae. - Lindahl, L (1994)
We have extended the system of Nogi et al. (Proc. Natl. Acad. Sci. USA 88, 1991, 3962-3966) for transcription of rRNA from an RNA polymerase II promoter in strains lacking functional RNA polymerase I. In our strains two differentially marked rRNA transcription units can be expressed alternately. Using this system we have shown that the A2 processing site in the internal transcribed spacer 1 (ITS1) of the pre-rRNA is dispensable. According to the accepted processing scheme, the A2 site serves to separate the parts of the primary rRNA transcript that are destined for incorporation into the two ribosomal subunits. However, we have found that, when A2 is impaired, separation of the small and large subunit rRNAs occurs at a processing site further downstream in ITS1, indicating that alternate pathways for ITS1 processing exist. Short deletions in the A2 region still allow residual processing at the A2 site. Mapping of the cleavage sites in such deletion transcripts suggests that sequences downstream of the A2 site are used for determining the position of the cleavage.